Acetazolamide and exercise hypoxia - Lafleur, J. E.; Bartniczuk, D.; Collier, A.; Griffin, N.; Swenson, E. R. (International Journal of Sports Medicine, 2010)
Acetazolamide is useful for acclimatizing to high altitude. How long it should be taken, and the physiological consequences of stopping it have not been thoroughly studied. We investigated the effect of acetazolamide cessation on exercise oxygenation at different altitudes and durations of use. Three groups were studied: group 1 acclimatized to 4 060 m for 6 days while taking acetazolamide 250 mg three times a day. On day 7 acetazolamide was stopped, then resumed on day 8. Standardized exercise oximetry was performed each day. The protocol for group 2 was identical to group 1, except acclimatization occurred over 14 days to 4 120 m. The protocol for group 3 was identical to group 2, except subjects acclimatized to 4 770 m. Multivariate regression revealed a negative effect of stopping acetazolamide on exercise oxygenation (p=0.028). At 4 100 m cessation of acetazolamide after one week resulted in a 11% drop in exercise oxygenation (p=0.008); after two weeks acclimatization to this altitude there was an non-significant drop in exercise oxygenation (2.5% p=0.064). At 4 770 m acetazolamide cessation resulted in an increase in exercise oxygenation (7% p=0.027). We conclude that exercise oxygenation after acetazolamide cessation is dependent both on duration of acclimatization/drug administration, and acclimatization altitude.